The Effect of Humanistic Nursing Practices on Compliance of Taking Medication in Hypertensive Patients in the Working Area of the Public Health Center - Trivonia Sri Nurwela; Israfil Israfil; Maria Agustina Making (Indonesian Journal of Global Health Research, 2021)
Hypertension is a chronic non-communicable disease that has threatened the health of Indonesian people. Hypertension complications have resulted in various types of disability and death. One of the factors causing complications of hypertension is patients’ non-compliance in taking anti-hypertension drugs. The purpose of this study was to determine the effect of humanistic nursing practice on compliance in taking medication for hypertensive patients in the working area of Public Health Center in Sikumana, Kupang City, East Nusa Tenggara Province, Indonesia. This experimental research method was conducted through a quasi-experimental design. The number of samples were 20 hypertensive patients who were taken by purposive sampling technique. The study sample was divided into two groups, namely the treatment group consisting of 10 patients and the control group consisting of 10 patients with inclusion criteria. The instruments used in the study were nurses worked as a therapist and a checklist to control the medication compliance. Therapy was given using the humanistic nursing practice therapy. The results of the study in the treatment group showed that 40% of the patients never took medication while 60% of the patients took medication occasionally. The reason for not taking medicine was because there were no complaints by 50%, herbal medicine consumption by 30% and running out medicine by 20%. The results of Manwhitney Test analysis of pre and post treatment obtained α = 0.000, z = -4.11. It can be concluded that there was a significant effect of humanistic nursing practice on the compliance in taking medication for hypertensive patients at the Public Health Center in Sikumana. Patients who were given humanistic nursing practice had 4.11 times greater compliance than patients who did not receive humanistic nursing practice services.